Epigenetic Changes Induced by High Glucose in Human Pancreatic Beta Cells - Rasha A. Alhazzaa; Raechel E. McKinley; Bruk Getachew; Yousef Tizabi; Thomas Heinbockel; Antonei B. Csoka (Journal of Diabetes Research)
Epigenetic changes in pancreatic beta cells caused by sustained high blood glucose levels, as seen in prediabetic conditions, may contribute to the etiology of diabetes. To delineate a direct cause and effect relationship between high glucose and epigenetic changes, we cultured human pancreatic beta cells derived from induced pluripotent stem cells and treated them with either high or low glucose, for 14 days. We then used the Arraystar 4x180K HG19 RefSeq Promoter Array to perform whole-genome DNA methylation analysis. A total of 478 gene promoters, out of a total of 23,148 present on the array (2.06%), showed substantial differences in methylation (p<0.01). Out of these, 285 were hypomethylated, and 193 were hypermethylated in experimental vs. control. Ingenuity Pathway Analysis revealed that the main pathways and networks that were differentially methylated include those involved in many systems, including those related to development, cellular growth, and proliferation. Genes implicated in the etiology of diabetes, including networks involving glucose metabolism, insulin secretion and regulation, and cell cycle regulation, were notably altered. Influence of upstream regulators such as MRTFA, AREG, and NOTCH3 was predicted based on the altered methylation of their downstream targets. The study validated that high glucose levels can directly cause many epigenetic changes in pancreatic beta cells, suggesting that this indeed may be a mechanism involved in the etiology of diabetes.